Moving diversily towards the green economy. CO2 abating techno-organizational trajectories and environmental policy in EU sectors - Mazzanti, Massimiliano; Rizzo, Ugo (Ferrara, 2014)
"This paper investigates, from ex ante perspectives, potential techno- organisational dynamics aimed at reducing GHG emissions in the EU by 2030 and 2050. We take a qualitative view by exploiting interviews with representatives from principal manufacturing sectors in the EU. The novel value of this analysis is in its focus on 'sectors', which, following neo-Schumpeterian theory, are key 'players' in the technological domain. From a conceptual point of view, we mainly refer to the integrated concepts of sector and national systems of innovation which have consolidated into innovation-oriented evolutionary theory: The EU is characterized by national sector specialisations that emerge from historical developments and markets effects, but also from industrial, innovation and environmental policy effects. In this way this work complements more consolidated quantitative econometric and modelling based analyses, as it presents sector-specific techno-organisational options to help reach the decarbonisation targets. We assess the feasibility of those targets from technological and economic perspectives: specific emphasis is put on the smooth or 'radical' change-driven transition towards a greener economy. Both market and policy factors are considered. The assessment of experts' qualitative responses, together with main outcomes from the literature, shows that heavy industrial sectors share some similarities but also key distinctions in relation to their past and future responses to market and policy dynamics. Their specificities should be taken into consideration when defining the specific design of the future EU policy package for energy efficiency and CO2 abatement at EU and national levels."